Radiation damage in flexible TFTs and organic detectors - Almeida, Maria Teresa Gonçalves Lobato de (2016)
In this thesis was investigated the radiation hardness of the building blocks of a future flexible X-ray sensor system. The characterized building blocks for the pixel addressing and signal amplification electronics are high mobility semiconducting oxide transistors (HMSO-TFTs) and organic transistors (OTFTs), whereas the photonic detection system is based on organic semiconducting single crystals (OSSCs). TFT parameters such as mobility, threshold voltage and subthreshold slope were measured as function of cumulative X-ray dose. Instead for OSSCs conductivity and X-ray sensitivity were analysed after various radiation steps. The results show that ionizing radiation does not lead to degradation in HMSO-TFTs. Instead OTFTs show instability in mobility which is reduced up to 73% for doses of 1 kGy. OSSC demonstrate stable detector properties for the tested total dose range. As conclusion, HMSO-TFTs and OSSCs can be readily employed in the X-ray detector system allowing operation for total doses exceeding 1 kGy of ionizing radiation.